2014
DOI: 10.1039/c4lc00248b
|View full text |Cite
|
Sign up to set email alerts
|

Digital biology and chemistry

Abstract: This account examines developments in "digital" biology and chemistry within the context of microfluidics, from a personal perspective. Using microfluidics as a frame of reference, we identify two areas of research within digital biology and chemistry that are of special interest: (i) the study of systems that switch between discrete states in response to changes in chemical concentration of signals, and (ii) the study of single biological entities such as molecules or cells. In particular, microfluidics accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 36 publications
0
70
0
1
Order By: Relevance
“…Our hypothesis is that that the confinement of samples containing low-abundance miRNAs in picoliter droplets can significantly increase the effective miRNA concentration, provide a means for digital quantification (i.e., each droplet has 0 or 1 target miRNA) and minimizes the number of background molecules (interference) from plasma. 25 Indeed, we demonstrated that the IC 3D can robustly quantify target miRNA directly from unprocessed plasma as validated by RT-qPCR for the same samples (Figure 3f). RNase-treated plasma was also included as a negative control to confirm that the fluorescent droplets are due to the target Let-7a (Figure s5).…”
Section: Resultsmentioning
confidence: 55%
“…Our hypothesis is that that the confinement of samples containing low-abundance miRNAs in picoliter droplets can significantly increase the effective miRNA concentration, provide a means for digital quantification (i.e., each droplet has 0 or 1 target miRNA) and minimizes the number of background molecules (interference) from plasma. 25 Indeed, we demonstrated that the IC 3D can robustly quantify target miRNA directly from unprocessed plasma as validated by RT-qPCR for the same samples (Figure 3f). RNase-treated plasma was also included as a negative control to confirm that the fluorescent droplets are due to the target Let-7a (Figure s5).…”
Section: Resultsmentioning
confidence: 55%
“…Optical single-molecule detection methods, also known as digital assays [68], have become valuable analytical techniques for a broad variety of bio-assays, enabling sensitive detection of relevant biomolecules down to the attomolar range. This ultrasensitive detection is possible by the isolation of individual target biomolecules into small reaction chambers where the signal is generated and detected.…”
Section: Digital Assaysmentioning
confidence: 99%
“…We found that pumping proceeded to completion despite the variation of pressure applied to the pumping lid by the volunteer. 30, 31 We expect the simplicity of the pumping lid to be valuable in both LRS and laboratory settings, e.g. for digital single-molecule measurements.…”
Section: Use Of Pumping Lids To Load Slipchip Devices By Positive Andmentioning
confidence: 99%